2019
DOI: 10.1002/aur.2152
|View full text |Cite
|
Sign up to set email alerts
|

Needs assessment in genetic testing education: A survey of parents of children with autism spectrum disorder in the united states

Abstract: Understanding parents' educational needs concerning genetic testing for their children with autism spectrum disorder (ASD) is important in developing tailored, evidence-based health education materials for clinical use. Since research is lacking in this area, to bridge the gap, we examined genetic testing education needs using a nationwide sample of parents of biological children with ASD in the United States. Prospective participants were recruited from the interactive autism network, and 552 parents of biolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 41 publications
2
14
0
1
Order By: Relevance
“…Studies have shown the importance parents place on information about genetic testing (Li et al, 2016 ; Zhao et al, 2019b ). Zhao et al ( 2019 ) demonstrated that most parents (73.7%) of a child with ASD, who was undergoing genetic testing, were interested in receiving health education on genetic testing (Zhao et al, 2019b ).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown the importance parents place on information about genetic testing (Li et al, 2016 ; Zhao et al, 2019b ). Zhao et al ( 2019 ) demonstrated that most parents (73.7%) of a child with ASD, who was undergoing genetic testing, were interested in receiving health education on genetic testing (Zhao et al, 2019b ).…”
Section: Discussionmentioning
confidence: 99%
“…Some participants indicated that their preferred modes would be e‐book and short online videos. These modes of education were also found to be preferable by clients for other health topics (e.g., Hernan et al, 2019; Zhao et al, 2019). However, the effectiveness of each medium needs to be tested.…”
Section: Discussionmentioning
confidence: 99%
“…Zahlreiche Eltern von Kindern mit ASS sowie auch Geschwister stellen die Frage nach dem Wiederholungsrisiko, sodass auch primär psychiatrisch tätige Personen zumindest grundsätzlich darüber Bescheid wissen sollten. Deutsche und internationale Studien haben sowohl ein hohes Interesse der Angehörigen als auch die Notwendigkeit einer grundlegenden Psychoedukation hinsichtlich genetischer Grundbegriff e und Schlussfolgerungen aus genetischen Tests gezeigt (Mey, Jenke & Borusiak, 2019;Zhao et al, 2019). Hinsichtlich vererbter monogener Erkrankungen sind die wesentliche Aspekte, die das Wiederholungsrisiko beeinfl ussen, die autosomal rezessive und dominante Vererbung sowie X-chromosomal rezessive und dominant vererbte Varianten.…”
Section: Translation In Die Praxisunclassified